Mobile receipt system - Zulhaimi, Zulkefli (2019)
Mobile Receipt System is an inventive system that manages and organizes receipt purchased. The system was developed with the web-based and Android application platform that interact and change information to deliver a practical system to the user. The system is designed for the retailer as their payment and receipt management system. The main problem is, the customer has a problem when storing all their receipt and required a lot of time to organize all their receipts. The system has offers five function that is login, add an item, generate a receipt, scan the receipt and add a list item. The system generates a digital receipt that can be retrieved using the Android application. The Android application of Mobile Receipt System manage and organize the receipt for the user. The system is using QR code features as a medium to interact with the web-based system and the application. Mobile Receipt was developed using the Agile methodology that includes iteration and incremental delivery during the development process. To make sure the system matches the expected result, the Black-box testing has been done to find bugs, defect or error in the system. The Black-box testing has been chosen because it will test the functionality of the system based on the requirement. From this project, the system is able to perform its functionality and fulfil the user expectation to help the user manage and organize all their receipts.